Asymptomatic Plasmodium Parasites among Adults in Eastern Uganda: A Case of Donor Blood Screening at Mbale Regional Blood Bank - Simon Peter Inyimai; Mosses Ocan; Benjamin Wabwire; Peter Olupot-Olupot (Journal of Tropical Medicine)
Background. There is a paucity of data on asymptomatic carriage of Plasmodium parasite among adult population in Eastern Uganda, an area of perennial high transmission of malaria. In this study, we estimated the prevalence of Plasmodium parasites in donor blood units at Mbale Regional Blood Bank (Mbale RBB), a satellite centre of the Uganda Blood Transfusion Service (UBTS). Method. This was a cross-sectional descriptive study in which 380 screened donor blood units were examined for the presence of Plasmodium parasites. A systematic random sampling technique using the interval of 7 was used in selecting the screened blood units for testing. Two experienced malaria slide microscopists (MC1 and MC2) independently examined each thick and thin blood slide under high power magnification of X400 and then X1000 as stated on the study standard operation procedure (SOP). Each slide was examined for 100 oil immersion fields before the examiner declared them negative for Plasmodium parasites. The results by each microscopist’s examination were tallied separately, and finally, the two tallies were compared. The third independent microscopist (MC3) was blinded to the results from MC1 and MC2, but whose role was to perform quality control on the slides randomly sampled and read 38 (10%) of all the slides and was available to examine any slides with inconsistent findings by MC1 or MC2. Results. All the microscopists were unanimous in all the slide readings. Five of the thick smears (1.3%) confirmed the presence of Plasmodium parasites among donor blood units. Of these, 4/5 were from male donors. Plasmodium falciparum was identified in 4 positive samples, while Plasmodium malariae was identified in one of the donor units. Conclusion. The 1.3% prevalence of Plasmodium malaria parasites in screened donor blood units represents risk of malaria blood transfusion transmitted infection and a pool of community transmittable malaria infections, respectively.